Transcriptome analysis reveals defense-related genes and pathways against Xanthomonas campestris pv. vesicatoria in pepper (Capsicum annuum L.) - Gao, Shenghua (PLoS One, 2021)
Bacterial spot (BS), incited by Xanthomonas campestris pv. vesicatoria (Xcv), is one of the most serious diseases of pepper. For a comparative analysis of defense responses to Xcv infection, we performed a transcriptomic analysis of a susceptible cultivar, ECW, and a resistant cultivar, VI037601, using the HiSeq(TM) 2500 sequencing platform. Approximately 120.23 G clean bases were generated from 18 libraries. From the libraries generated, a total of 38,269 expressed genes containing 11,714 novel genes and 11,232 differentially expressed genes (DEGs) were identified. Functional enrichment analysis revealed that the most noticeable pathways were plant-pathogen interaction, MAPK signaling pathway—plant, plant hormone signal transduction and secondary metabolisms. 1,599 potentially defense-related genes linked to pattern recognition receptors (PRRs), mitogen-activated protein kinase (MAPK), calcium signaling, and transcription factors may regulate pepper resistance to Xcv. Moreover, after Xcv inoculation, 364 DEGs differentially expressed only in VI037601 and 852 genes in both ECW and VI037601. Many of those genes were classified as NBS-LRR genes, oxidoreductase gene, WRKY and NAC transcription factors, and they were mainly involved in metabolic process, response to stimulus and biological regulation pathways. Quantitative RT-PCR of sixteen selected DEGs further validated the RNA-seq differential gene expression analysis. Our results will provide a valuable resource for understanding the molecular mechanisms of pepper resistance to Xcv infection and improving pepper resistance cultivars against Xcv.